PERLINDUNGAN HUKUM PADA PEREMPUAN SEBAGAI KORBAN DALAM PEREDARAN NARKOTIKA DIKAITKAN DENGAN TUJUAN PEMIDANAAN - Aisyah Nur Roma Dani; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The crime of narcotics circulation has taken many victims, including takingadvantage of the circumstances of women living unfit to be couriers in circulating narcotics.Many of the factors that cause women to be involved not by personal desires aregeographical, economic, and sociological factors. Legal protection tends to be abstract andregulatory, which can not accommodate the rights of victims of narcotics trafficking. If theregulation has not been able to meet the needs of the victims, it certainly harms the basicrights held by the victim, especially those who are sentenced to death, especially those whoare included in the crime victim classification, of course this is very against the purpose ofconviction and death. The purpose of this study: First, the application of legal protection towomen as victims in narcotics circulation if it is linked to the purpose of conviction, Second,understand the legal weakness in providing legal protection to women as victims in narcoticscirculation in Indonesia, Third,provide legal efforts to protect women as victims of narcoticstrafficking.This study is classified as a type of normative legal research that examines librarymaterials. This study examines the legal principles approach by examining the rules of law inrelated regulations relating to legal issues to be examined. Data sources are secondary dataconsisting of primary legal materials, secondary legal materials and tertiary legal materials.The data collection technique in this study is a library research method.The results that can be obtained from this study are three points of conclusion,namely: First, in providing legal protection tends to be abstract by imposing penalties onperpetrators who are considered by some parties to meet the suffering experienced byvictims. Victims do not get the right to do legal defense and when sentenced to death, it isclearly against human rights and the purpose of conviction. Second, the regulation regardinglegal protection on victims of narcotics circulation from the regulation has not been able tomeet the needs of the victims. Third, the role of the government has a big part in making legalefforts on narcotics crimes, one of which is by carrying out criminal policies based on justice.The author suggested, First, it is necessary to renew legal efforts in the law on narcoticscrimes that accommodate the rights of the victims. Second, socializing creative media in thepublic about the drug campaign of narcotics crime. Third, the Government can pay moreattention to them as victims of crime and budget the State Budget and maximize the body ofrehabilitation in every affected area.Keywords: Legal Protection-Women-Victims-Narcotics-Purpose of Sentencing